Crystal structure and biochemical analyses reveal that the Arabidopsis triphosphate tunnel metalloenzyme AtTTM3 is a tripolyphosphatase involved in root development. (17th October 2013) - Moeder, Wolfgang; Garcia‐Petit, Christel; Ung, Huoi; Fucile, Geoffrey; Samuel, Marcus A.; Christendat, Dinesh; Yoshioka, Keiko
Summary: The Arabidopsis protein AtTTM3 belongs to the CYTH superfamily named after its two founding members, the CyaB adenylate cyclase from Aeromonas hydrophila and the mammalian thiamine triphosphatase. In this study we report the three‐dimensional structure of a plant CYTH domain protein, AtTTM3, determined at 1.9 Å resolution. The crystal structure revealed the characteristic tunnel architecture of CYTH proteins, which specialize in the binding of nucleotides and other organic phosphates and in phosphoryl transfer reactions. The β barrel is composed of eight antiparallel β strands with a cluster of conserved inwardly facing acidic and basic amino acid residues. Mutagenesis of these residues in the catalytic core led to an almost complete loss of enzymatic activity. We established that AtTTM3 is not an adenylate cyclase. Instead, the enzyme displayed weak NTP phosphatase as well as strong tripolyphosphatase activities similar to the triphosphate tunnel metalloenzyme proteins from Clostridium thermocellum (CthTTM) and Nitrosomonas europaea (NeuTTM). AtTTM3 is most highly expressed in the proximal meristematic zone of the plant root. Furthermore, an AtTTM3 T‐DNA insertion knockout line displayed a delay in root growth as well as reduced length and number of lateral roots, suggesting a role for AtTTM3 in root development.